Cross gain modulation in quantum dot semiconductor optical amplifiers under the influence of the Probe - Flayyih, Ahmed; Seyedeh Hamideh Kazemi; Al-Khursan, Amin (University of Thi-Qar Journal of Science, 2023)
The Pulse effect on the  cross-gain modulation (XGM) in the quantum dot (QD) semiconductor optical amplifiers (SOAs) is investigated using the combining of the SOA power with the QD rate equations system. The QDs structure  includes  three regions: ground state (GS), excited state (ES) and wetting layer (WL). Thus, a set of rate equations for pump and probe signals is introduced for both steady-state and small-signal power values, which are solved numerically. The pulse shape was included in the analysis, for pump and probe signals.  The theoretical results showed a good agreement with the experimental results. It was found that decreasing pulse width of pump/probe ratio is efficient to increase XGM efficiency and bandwidth.